2020
DOI: 10.1002/nau.24285
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled study of the efficacy of tadalafil monotherapy versus combination of tadalafil and mirabegron for the treatment of persistent overactive bladder symptoms in men presenting with lower urinary tract symptoms (CONTACT Study)

Abstract: A randomized controlled study of the efficacy of tadalafil monotherapy versus combination of tadalafil and mirabegron for the treatment of persistent overactive bladder symptoms in men presenting with lower urinary tract symptoms (CONTACT Study) Abstract Aim: To evaluate efficacy and safety of combination of tadalafil + mirabegron for overactive bladder/benign prostatic hyperplasia (OAB/BPH). Methods: Male patients with lower urinary tract symptoms (50 to 89 years), with remaining OAB symptoms even after admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 20 publications
1
35
1
Order By: Relevance
“…We screened 10 full-text articles and excluded 6 articles that did not meet the inclusion criteria or were not relevant to the question being investigated [12,[19][20][21][22][23] (see Supplementary Material 2). Four studies ultimately met the inclusion criteria were included in the qualitative synthesis of this review [24][25][26][27]. The flow of literature through this assessment process is shown in the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flowchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We screened 10 full-text articles and excluded 6 articles that did not meet the inclusion criteria or were not relevant to the question being investigated [12,[19][20][21][22][23] (see Supplementary Material 2). Four studies ultimately met the inclusion criteria were included in the qualitative synthesis of this review [24][25][26][27]. The flow of literature through this assessment process is shown in the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flowchart (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows baseline characteristics of the included studies. Three studies [24,26,27] were open-label studies, while one study [25] was double-blinded. The mean age of the men ranged from 64.9 to 75.9 years old.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study also reported improved symptoms for mirabegron in combination with a phosphodiesterase 5 inhibitor, tadalafil 5 mg ( n = 89), compared with tadalafil monotherapy ( n = 87) in male patients aged ≥ 50 years with residual OAB symptoms [ 18 ]. The primary endpoint, change from baseline in total OABSS, was statistically significantly decreased by 1.78 (95% CI 1.05–2.50) points in the combination group compared with the monotherapy group ( P < 0.001).…”
Section: Discussionmentioning
confidence: 99%